EFISIENSI YANG TINGGI MERUPAKAN SYARAT UTAMA MEMENANGKAN PERSAINGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI - R Gatot Heru Pranjoto (Universitas Trunojoyo Madura, 2018)
ABSTRACTCompetition is won by the company with high efficiency, which in its operation has high operating leverage, it means the increase of operating profit followed by higher output increase, hence the increase of fixed cost, can decrease higher variable cost. High degree of operating can be obtained through several factors, among others through cost efficiency, partnerships with customers and continuous improvement